2010
DOI: 10.1016/j.visres.2010.01.008
|View full text |Cite
|
Sign up to set email alerts
|

A dual-stage account of inter-trial priming effects

Abstract: The study of inter-trial effects in visual search has generated an increasing amount of research in recent years. However, the mechanisms underlying these effects are still a matter of debate. Two rival accounts have been suggested. One view stipulates that inter-trial effects facilitate early perceptual/attentional processes, whereas the other proposes that it affects post-perceptual response-related processes. Here, we focused on the priming of pop-out effect (PoP, Maljkovic & Nakayama, 1994), which refers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
80
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 24 publications
21
80
0
Order By: Relevance
“…For instance, distractor repetition speeds search even when target features are not repeated (e.g., Kristjánsson & Driver, 2008), suggesting that some form of distractor suppression or discounting also plays a role. Other evidence has suggested that priming can also happen at the response selection stage (Lamy, Yashar, & Ruderman, 2010;. This has been observed in complex visual search arrays, which make it difficult to disentangle between the various possible mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, distractor repetition speeds search even when target features are not repeated (e.g., Kristjánsson & Driver, 2008), suggesting that some form of distractor suppression or discounting also plays a role. Other evidence has suggested that priming can also happen at the response selection stage (Lamy, Yashar, & Ruderman, 2010;. This has been observed in complex visual search arrays, which make it difficult to disentangle between the various possible mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work from our lab however, has shown that the number of trials over which PoP can be measured is strongly affected by contextual reinstatement that is both perceptual (Thomson & Milliken, 2012) and nonperceptual (Thomson & Milliken, in press) in nature, suggesting that retrieval interference may at least partially dictate the magnitude of PoP effects. In addition, recent theoretical accounts of PoP have been forwarded that acknowledge a role for both feed-forward mechanisms, as well as episodic retrieval contributions to the PoP effect (Lamy, Yashar, & Ruderman, 2010;Yashar & Lamy, 2011). As a result, the attentional control over the magnitude of PoP shown in the present work could result from either control over feature weights from one trial to the next or control over event integration, if indeed both such processes contribute to PoP effects.…”
Section: Discussionmentioning
confidence: 67%
“…In particular, it has been suggested that facilitatory effects observed in intertrial priming may be an "aggregate" of early perceptual-processing benefits in directing focal attention to the odd-ball target, in addition to later memory retrieval benefits that impact response-related processing (Lamy, Yashar, & Ruderman, 2010). An important implication of this hybrid view is that recent studies showing that episodic retrieval can impact singleton search performance from one trial to the next does not preclude the presence of early perceptual-processing benefits that are due to activation/ suppression mechanisms.…”
mentioning
confidence: 99%